The Influence of Multiple Intelligences on Employee Performance and Its Impact on Future Career Advancement - Santoso, Arief Budi; Vin, Ong Ma (Ilomata International Journal of Management, 2026)
This study examines the influence of multiple intelligences on employee performance and its impact on future career advancement. Grounded in Gardner’s Multiple Intelligence Theory and Human Capital Theory, although Multiple Intelligence Theory identifies eight types of intelligence, this research operationalizes five dimensions that are more applicable to organizational contexts, namely linguistic, logical–mathematical, interpersonal, intrapersonal, and spatial–bodily kinesthetic intelligence, which, in shaping employee performance, in turn affects career progression. The study involved 320 respondents employed in eight service and manufacturing firms operating in the Greater Tangerang industrial region. These companies were purposively selected to represent different industries, and employees were recruited through voluntary survey participation. The hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) implemented through SmartPLS, allowing simultaneous assessment of measurement validity and structural relationships. The results indicate that multiple intelligences have a significant positive effect on employee performance, and employee performance significantly influences future career advancement. Furthermore, employee performance mediates the relationship between multiple intelligences and career advancement. These findings enrich human resource management theory while simultaneously providing practical guidance for talent development initiatives and structured career planning within organizations.